Report on maternity insurance (London : Co-operative Printing Society Ltd., 1927)
1927 1927 1920s 16 pages 4 The efforts of the voluntary agencies and their representations as to the unnecessary suffering and loss of life entailed by ignorance, no doubt stimulated public opinion, and in 1907, the Notification of Births Act was passed. This Act was the origin of the maternity work of the present day, as the registration of births opened the way for systematic visiting in the home. But as the Act was adoptive and not compulsory, the authorities entitled to adopt its provisions were not bound to do so, and very little was done until 1915, when the Notifications of Births Extension Act was passed, by which notification within 36 hours of a birth was made compulsory on all Local Authorities. The year before, authority had been given to the Local Government Board to give grants to Local Authorities for maternity work, but the position was ambiguous, and the power under the Public Health Act did not really cover starting maternity centres, which had to figure as hospitals in order to get a grant. In 1918, the Maternity and Child Welfare Act was passed. Under this Act the grant given by the Local Government Board was increased to 50 per cent. of the expenditure of Local Authorities and voluntary agencies so far as their arrangements were sanctioned by the Board. The grants from the Local Government Board (now the Ministry of Health) are given for a very large range of services which aim at safeguarding the lives of the infant and mother. These are :— 1. The salaries and expenses of Inspectors of Midwives. 2. The salaries and expenses of Health Visitors and Nurses engaged in Maternity and Child Welfare work. 3. The provision of a Midwife for necessitous women in confinement, and for areas which are insufficiently supplied with this service. 4. The provision, for necessitous women of a doctor for illness connected with pregnancy, and for aid during the period of confinement for mother and child. 5. The expenses of a Centre, i.e., an institution providing any or all of the following activities : Medical supervision and advice for expectant and nursing mothers, and for children under five years of age, and medical treatment at the Centre for cases needing it. 6. Arrangements for instruction in the general hygiene of maternity and childhood. 292/824/1/114